Elastic scattering of 8B+90Zr at sub-barrier energies - Palli, K.; Pakou, A.; Moro, A. M.; O'Malley, P. D.; Acosta, L.; Sántzez-Bénitez, A.; Souliotis, G.; Aguilera, E. F.; Andrade, E.; Godos, D.; Sgouros, O.; Soukeras, V.; et al. (HNPS Advances in Nuclear Physics, 2024)
Elastic scattering measurements for the reaction 8B+90Zr at the sub-barrier energy of 26.5 MeV (~ 0.9 VC.B.) were carried out in a recent experiment, realized at the TriSol radioactive beam facility of the University of Notre Dame. This experiment was performed in continuation of our previous work studying 8B on the heavier target 208Pb, alongside with breakup measurements for the same reaction. Final goal is the determination of total reaction and breakup cross sections and the deduction of the direct to total cross section ratio. Preliminary experimental data for elastic scattering will be presented and compared with OMP and CDCC calculations.